Keunggulan Imunositokimia GATA3 Dibandingkan Mammaglobin dan GCDFP-15 untuk Menentukan Metastasis Karsinoma Payudara pada Sitologi Blok Sel Cairan Pleura - Devi Felicia; Tantri Hellyanti (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction: Determination of the primary tumor of a malignant pleural effusion is needed for an appropriate management. The most common etiologies of malignant pleural effusion are cancer of the lung, breast, lymphoma, etc. Mammaglobin (MGB) and gross cystic disease fluid protein 15 (GCDFP15) are currently used as breast specific markers in Indonesia. GATA binding protein 3 (GATA3) has recently reported to have a better diagnostic accuracy. Purpose: To compare the accuracy of GATA3 and MGB/GCDFP-15 as breast specific marker in determining the primary tumor of a malignant effusion cytology specimen.Methods: We searched Pubmed, Cochrane, Proquest, Scopus, EBSCOHost, and found 7 relevant articles to be appraised.Result: With various positive cutoffs, the accuracy of GATA3 for cell blocks of effusion is significantly better than MGB and GCDFP-15, with sensitivity of 90-93,5% and specificity of 88,5-96,9%. The staining intensity of GATA3 was also higher, with less background staining so that reading and interpretation could be done easier.Conclusion: The accuracy of GATA3 as a breast specific marker to determine the primary tumor of a malignant effusion cell block is better than MGB and GCDFP-15. Thus, GATA3 may be considered to be used as a breast specific marker to replace MGB and GCDFP-15.